Numeration Literacy Of PGMI UIN Raden Intan Lampung Students In Solving Mathematical Problems - Agustina, Julia; Ifrianti, Syofnidah; Negara, Hasan Sastra (Universitas Maritim Raja Ali Haji, 2023)
This study aims to describe the numeracy literacy skills of PGMI students at UIN Raden Intan Lampung in solving math problems. Referring to the results of international surveys, one of which is PISA, Indonesian students' achievements are still below the global average score. Therefore, PGMI as one of the study programs, is expected to be able to produce qualified MI teachers. As prospective teachers, PGMI students must have the ability to think at a high level. The data obtained shows that the numeracy literacy skills of students still need to be analyzed further to determine the level of numeracy literacy skills. The research method used is the qualitative descriptive analysis method. The instruments used were descriptive tests and interviews. Data analysis used in this study uses the following steps: Data Reduction, Data Display, and Verification. The subjects in this study were 91 PGMI students in the class of 2020. The results showed that the numeracy skills of PGMI UIN Raden Intan Lampung class 2020 students in solving math problems were sufficient. This is shown in the research results that only 22.09% of students can use various kinds of numbers and symbols in the first indicator, 13.08% of students can analyze information displayed in various forms in the second indicator, and only 4.36% can interpret all analysis questions to make the right decision in the third indicator.